On an Inverse Boundary Value Problem for a Fourth Order Elliptic Equation with Integral Condition - Yashar T. Mehraliyev (Abstract and Applied Analysis)
An inverse boundary value problem for a fourth order elliptic equation is investigated. At first the initial problem is reduced to the equivalent problem for which the existence and uniqueness theorem of the solution is proved. Further, using these facts, the existence and uniqueness of the classic solution of the initial problem are proved.